Assessment of corticospinal tract (CST) damage in acute stroke patients: Comparison of tract‐specific analysis versus segmentation of a CST template. Issue 4 (19th October 2012) - Vargas, Patricia; Gaudron, Marie; Valabrègue, Romain; Bertasi, Eric; Humbert, Frédéric; Lehéricy, Stéphane; Samson, Yves; Rosso, Charlotte
Abstract Purpose: To compare two techniques to assess corticospinal tract (CST) damage in stroke patients: tract‐specific analysis by probabilistic tractography and segmentation using a CST template. Materials and Methods: We extracted fractional anisotropy (FA) values, the FA ratio, and mean diffusivity (MD) in 18 stroke patients and 21 healthy volunteers matched for age and sex. We compared the two methods in order to determine their ability to detect 1) differences between diffusion tensor imaging (DTI) parameters of healthy volunteers and stroke patients, 2) the correlation between DTI parameters and clinical scores, and 3) the correlation between DTI parameters and blood oxygen level‐dependent (BOLD) signals in a fist‐closure task. Results: FA values were higher with the tractography approach than with the segmentation method, but differences between the ipsilesional CST and the homologous region in healthy subjects were detected using both methods. In patients, clinical scores were significantly correlated with FA values and FA ratios with both methods. The BOLD signal was positively correlated with FA values for CST with the segmentation but not with the tractography approach. Conclusion: CST damage in stroke patients can be assessed by either probabilistic tractography or segmentation of a CST template. Although each method has advantages and limitations, both are sensitive enough to detect differences among stroke patients and identify specific correlations with clinical scores. J. Magn. Reson. Imaging 2013;37:836–845. © 2012 Wiley Periodicals, Inc.